Penerapan Media Animasi Berbasis Doratoon untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas VIII - Nurul Muchlisa Maulidya; Hasanuddin Hasanuddin; Sitti Rahma Yunus (Universitas Negeri Makassar, 2025)
This research aims to determine: 1) the level of learning motivation category of class VIII students at SMPN 27 Makassar before and after the application of Doratoon- based animation media. 2) the increase in learning motivation of class VIII students at SMPN 27 Makassar through the application of Doratoon- based animation media. 3) whether the application of Doratoon- based animation media can significantly increase learning motivation in class VIII students at SMP Negeri 27 Makassar. The types of this research are Pre- Experimental Design research and One Group Pretest- Posttest Design research design. The population of this research is all students in class VIII of SMP Negeri 27 Makassar for the 2023/2024 school year, the sample was 25 students selected by purposive sampling. The research instrument is a learning motivation questionnaire. Data were analyzed using descriptive and inferential statistics. The results of the analysis concluded: 1) the motivation category and learning outcomes of class VIII students at SMP Negeri 27 Makassar before application of Doratoon- based animation media obtained an average learning motivation score of 69.92 which was in the medium category, whereas after application of Doratoon- based animation media, an average learning motivation score of 76.76 was obtained, which was in the high category. 2) the increase in learning motivation of class VIII students at SMP Negeri 27 Makassar through the application of Doratoon- based animation media obtained an average N- Gain on learning learning motivation of 0.21 which is in the low category, 3) the determination of Doratoon- based animation media can significantly increase learning motivation in class VIII students at SMP Negeri 27 Makassar.